Sex differences and adherence of patients treated with wearable cardioverter-defibrillator: insights from an international multicenter register - Abumayyaleh, Mohammad S. A.; Dreher, Tobias C.; Rosenkaimer, Stephanie L.; Röger, Susanne; Erath, Julia W.; Klein, Norbert; Kovacs, Boldizsar; Duru, Firat; Saguner, Ardan M.; El-Battrawy, Ibrahim; Akın, Ibrahim (Journal of cardiovascular electrophysiology, 2022)
Aims: Treatment with the wearable cardioverter defibrillator (WCD) may protect against sudden cardiac death (SCD) as a bridging therapy until a cardioverter-defibrillator may be implanted. We analyzed in a multicenter setting a consecutive patient cohort wearing WCD to explore sex differences. Methods and Results: We analyzed 708 consecutive patients, 579 (81.8%) from whom were males and 129 (18.2%) females (age, 60.5 ± 14 vs. 61.6 ± 17 years old; p = .44). While the rate of ischemic cardiomyopathy (ICM) as a cause of prescription of WCD was significantly higher in males as compared to females (42.7% vs. 26.4%; p = .001), females received it more frequently due to nonischemic cardiomyopathy (NICM) (55.8% vs. 42.7%); p = .009). The wear time of WCD was equivalent in both groups (21.1 ± 4.3 h/days in males vs. 21.5 ± 4.4 h/days in females; p = .27; and 62.6 ± 44.3 days in males vs. 56.5 ± 39 days in females; p = .15). Mortality was comparable in both groups at 2-year-follow-up (6.8% in males vs. 9.7% in females; p = .55). Appropriate WCD shocks and the incidence of ICD implantations were similar in both groups (2.4% in males vs. 3.9% in females; p = .07) (35.1% in males vs. 31.8% in females; p = .37), respectively. In age tertile analysis, compliance was observed more in 73-91 years old group as compared with 14-51 years old group (87.8% vs. 68.3%; p < .001). Conclusion: Compliance for wearing WCD was excellent regardless of sex. Furthermore, mortality and the incidence of ICD implantations were comparable in both sexes. Appropriate WCD shocks were similar in both sexes.
Gesehen am 03.07.2023